PENERAPAN EKOWISATA MANGROVE BERBASIS MASYARAKAT DI DESA TELUK PAMBANG KECAMATAN BANTAN - Romy Luviana; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine: (1) the planning of community association in mangrove ecotourism area Teluk Pambang Village Bantan Subdistrict; (2) the community’s responsibility Teluk Pambang Village toward the development of mangrove tour in Teluk Pambang Village Bantan Subdistric. This study used a qualitative method in form of descriptive approach, some informant were taking as the subject of research and additional informant. The result of the research showed that the involvement of Teluk Pambang Villagers in protecting, developing and maintaining this mangrove ecotourism was in active. Only a few of them were participating. Their attendance, business iniciative and their business purpose in this area was still limited because of their own jobs at home. Mean while, the management position in organizing and playing role was done well as well as the number of mangrove object managed. Although, illegal logging was the main problem that caused obstade in maintenance and evaluation. At last, people see mangrove ecotourism in Teluk Pambang as a potential way to lift up their economic growth.Keywords: Ecotourism, Mangrove, Community Based.